Principles of welding processes physics chemistry and metallurgy - Messler, Robert W. (John Wiley & Sons, 1999)
"A comprehensive, self-contained treatment of the welding process along with the underlying physics, chemistry, and metallurgy of weld formation ... the standard text and reference in the field ... provides ... broad coverage of ... the mechanics of solidification--including peritectic and eutectic reactions ... hundreds of tables and illustrations"--Back cover.